The impact of producers' cognitive styles on their purchasing behavior - Feeney, Roberto Juan (2019)
This paper inquires on the impact of cognitive styles over the decision-making process producers perform while making input and capital equipment purchases. We will question if Argentine farmers with diverse cognitive styles have different purchasing behaviors when buying the inputs they use in their farming operations. Cognitive styles express differences in the way decision-makers process information and organize knowledge. Results show that different segments of producers have distinctive purchasing behaviors. Specifically, analytic-oriented producers tend to focus more on product performance and less on the relationship with suppliers when buying their inputs. They also tend to be loyal to input brands, they rely less on dealers/retailers and salespeople, and they are willing to change suppliers more often than other producers. Intuitive-oriented producers value more the relationship with the supplier and are interested in contacting the salesperson if they need a product. While balanced-oriented producers declare to be less loyal to brands but are more stable in terms of not changing input suppliers frequently. This characterization of producers has important business implications, since identifying and segmenting the different types of producers with different cognitive styles and distinctive buying profiles is a key aspect of the strategic marketing plan of any company in the input markets. To our knowledge, this is the first paper on the topic of cognitive styles of Argentine producers and their impact on their purchasing behaviors.